Effects of Rhizobium, molybdenum and cabalt on bean plants cv. Carioca - Corrêa, João Roberto Viana; Netto, Arnoldo Junqueira; Rezende, Pedro Milanez de; Andrade, Luis Antônio de Bastos (Pesquisa Agropecuaria Brasileira, 2014)
With the purpose of verifying the effects of Rhizobium phaseoli, molybdenum (Mo) and cobalt (Co) on yield and some traits of bean plant (Phaseolus vulgaris L), cultivar Carioca, and also establishing optimal doses for the micronutrients tested, an experiment was undertaken in greenhouse, on soil under "cerrado", classified as Dystrophic Dark Red Latossol clayey texture, at Escola Superior de Agricultura de Lavras, in Lavras, MG, Brazil. The experiment design was that of randomized bloks in factorial scheme 42 x 2 with three replicates. The treatments were made up by combining of four levels of Mo (0, 7, 14 and 21 g/ha) and Co (0, 0,3, 0,6 and 0,9 g/ha) applied as a solution via seeds in the presence and absence of inoculants. The results showed that the applying of the inoculant and Mo exercised benefic influences, helping all the characteristics evaluated. The greatest grain yield was obtained when applying 14 and 0,6 g/ha of Mo and Co, respectively. Applying Co singly did not influence either the number of pods per plant or grains per pod of bean plant